The Relationship between Parenting Style and the Level of Gadget Usage on Children's Aggressiveness in Insan Robbani Integrated Islamic Kindergarten Sibuhuan - Lubis, Nur Azizah; Rakimahwati, Rakimahwati; Yaswinda, Yaswinda; Nurhafizah, Nurhafizah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Proper parenting shapes healthy gadget use habits in early childhood, while uncontrolled parenting increases the risk of adverse impacts. This study aims to identify the relationship between parenting style and gadget usage in early childhood at the Insan Robbani Sibuhuan Integrated Islamic Kindergarten. The cross-sectional method with a quantitative approach and correlation research, along with the use of questionnaires, was chosen because it allows researchers to efficiently collect and analyze data on the relationship between gadget use and the level of aggressiveness in early childhood at a single point in time in a structured and objective manner. There were 63 children and parents as samples in this study. The quota sampling technique based on non-probability sampling is a sampling technique applied by researchers. In addition, questionnaires were also used to obtain data for this study. A reliability and validity test is applied as a research instrument test. The results indicate that parenting styles and gadget usage significantly influence the aggression levels of 68% of early childhood children at Insan Robbani Sibuhuan Integrated Islamic Kindergarten, with the remainder attributed to other factors.